2021
DOI: 10.1111/ppc.12800
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nursing interventions to instill hope on the internalized stigma, hope, and quality of life levels in patients With schizophrenia

Abstract: Purpose: This study was conducted to determine the effect of nursing interventions to instill hope on the internalized stigma, hope, and quality of life. Methods:The study was conducted as a quasi-experimental study with the experimental and control groups and repeated measurements. The data were collected using the Personal Information Form, Internalized Stigma Scale in Mental Illnesses (ISMI), Herth Hope Index (HHS), and Quality of Life Scale (QLS) for schizophrenia patients. Results:The difference between I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Tis study revealed that PPEW intervention can efectively reduce stigma in patients with schizophrenia. Many studies have shown that mindfulness, self-afrmation training, hope intervention, and other psychological interventions based on positive psychology [27][28][29] can decrease stigma in patients with schizophrenia, which is consistent with our fndings. However, the existing PPIs are mostly input-based and administered without focusing on the patient's output, and some are complicated in structure, inconvenient to implement, and costly.…”
Section: Discussionsupporting
confidence: 81%
“…Tis study revealed that PPEW intervention can efectively reduce stigma in patients with schizophrenia. Many studies have shown that mindfulness, self-afrmation training, hope intervention, and other psychological interventions based on positive psychology [27][28][29] can decrease stigma in patients with schizophrenia, which is consistent with our fndings. However, the existing PPIs are mostly input-based and administered without focusing on the patient's output, and some are complicated in structure, inconvenient to implement, and costly.…”
Section: Discussionsupporting
confidence: 81%
“…Schizophrenia is a chronic mental disorder characterized by positive and negative symptoms, including disability, the onset of which typical begins during adolescence or early adulthood, and for which a community‐based treatment should be viewed as a way to enhance treatment (Ercan & Demir, 2019; Özçelik & Yıldırım, 2018; Öztürk & Altun, 2021). In a systematic review of the psychosis epidemiology in Turkey, the lifetime prevalence of schizophrenia in general population was reported to be 8.9 per 1000 people (Binbay et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In schizophrenia, the side effects of drug treatment, cognitive and psychosocial impairment associated with the illness, negative symptoms, number of hospitalizations, social isolation, comorbid depression, unemployment, low self‐esteem, and stigmatization result in varying degrees of deterioration in the quality of life of those affected (Aykut et al, 2017; Dziwota et al, 2018; Öztürk & Altun, 2021; Vrbova et al, 2017). Quality of life, which consists of physical health, mental state, social relationships, and environmental dimensions, is used as an important tool in the reintegration of people with schizophrenia into society and in the evaluation of treatment and care (Ertekin et al, 2015, Woon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hope is an essential factor that initiates and accelerates the recovery process in schizophrenic individuals and an important coping mechanism that increases individuals' motivation while fighting the disease (Şahin Altun and Olçun 2018, Sari et al 2021, Öztürk and Şahin Altun 2022. In the studies conducted with individuals with schizophrenia, it was found that hope increases levels of functional improvement, self-efficacy, self-esteem, quality of life, and disease compliance (Lysaker et al 2009, Oles et al 2015, Vrbova et al 2017, Coşkun and Altun 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Although these tools have good validity and reliability, none of them have been validated for schizophrenic patients. In studies conducted in our country, the level of hope of individuals diagnosed with schizophrenia is frequently assessed with the Herth Hope Scale (HHS) (Olçun and Şahin Altun 2017;Kavak and Yılmaz 2018;Öztürk and Şahin Altun 2022). The Herth Hope Scale (HHS) was developed to evaluate hope in cancer patients and their families (Herth 1991).…”
Section: Introductionmentioning
confidence: 99%